2022
DOI: 10.5194/egusphere-egu22-10718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relaxing ETAS’s Assumptions to Better Capture the Real Behavior of Seismicity

Abstract: <p>When developing next-generation earthquake forecasting models, the key is to more carefully account for the real world (which has fault systems with different properties, site-specific properties, swarm-like episodes of temporally elevated seismicity, etc.), without constructing overly complicated models that are hard to comprehend and even harder to use. Finding the sweet spot between simplicity and accuracy is what constitutes the art of modelling. Epidemic-Type Aftershock Sequence (ETAS) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Amatrice-Visso-Norcia catalog produced by Tan et al (2021b) is accessible at the Zenodo repository https:// doi.org/10.5281/zenodo.4736089 (Tan et al, 2021a). The ETAS simulator used to generate the synthetic data was written for Mizrahi et al (2021aMizrahi et al ( , 2021b, and is available at https://github.com/lmizrahi/etas (Mizrahi & Schmid, 2022). Both synthetic and real data sets are found in the reproducibility package along with the models and the experimental design used in this study (Stockman, 2023)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The Amatrice-Visso-Norcia catalog produced by Tan et al (2021b) is accessible at the Zenodo repository https:// doi.org/10.5281/zenodo.4736089 (Tan et al, 2021a). The ETAS simulator used to generate the synthetic data was written for Mizrahi et al (2021aMizrahi et al ( , 2021b, and is available at https://github.com/lmizrahi/etas (Mizrahi & Schmid, 2022). Both synthetic and real data sets are found in the reproducibility package along with the models and the experimental design used in this study (Stockman, 2023)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The Amatrice-Visso-Norcia catalog produced by Tan et al (2021b) is accessible at the Zenodo repository https://doi.org/10.5281/zenodo.4736089 (Tan et al, 2021a). The ETAS simulator used to generate the synthetic data was written for Mizrahi et al (2021a) and Mizrahi et al (2021b), and is available at https://github.com/lmizrahi/etas, (Mizrahi & Schmid, 2022). Both synthetic and real datasets are found in the reproducibility package along with the models and the experimental design used in this study, found at https://github.com/ss15859/Neural-Point-Process.…”
Section: Open Researchmentioning
confidence: 99%